Improved solid-state conversion and piezoelectric properties of 90Na1/2Bi1/2TiO3-5BaTiO3-5K1/2Na1/2NbO3 single crystals. Issue 1 (January 2017) - Ko, Seok-Young; Park, Ji-Hoon; Kim, Ill-Won; Won, Sung-Sik; Chung, Sung-Yoon; Kang, Suk-Joong L.
Abstract: Na1/2 Bi1/2 TiO3 -BaTiO3 -K1/2 Na1/2 NbO3 (NBT-BT-KNN) is a promising candidate system for actuator applications in lead-free piezoelectric materials because of its large electric-field-induced strain. We were able to fabricate 96.9% dense 90NBT-5BT-5KNN (mol%) single crystals by the solid-state single crystal growth technique using sintered pellets and SrTiO3 seed crystals. The fabricated single crystals with a 〈001〉 direction exhibited high piezoelectric performance with a large strain of 0.67% and a high converse piezoelectric constant (Smax /Emax ) of about 1670 pm/V at 4 kV/mm. These values are much higher than those previously reported for ceramics, 0.45% and 560 pm/V at 8 kV/mm, and for single crystals, 0.57% and 950 pm/V at 6 kV/mm, of the NBT-BT-KNN system. The measured piezoelectric properties are even comparable with those of lead-containing piezoelectric single crystals, which demonstrates high applicability of the fabricated NBT-5BT-5KNN single crystals for actuators.